MISINTERPRETATION OF QUR'ANIC VERSES ON THE â€œISLAMICâ€ JIHAD - Yusuf, Choirul Fuad (Center for Research and Development of Religious Literature and Heritage, 2014)
The word jihad has been understood various way according to motive, objective, paradigm, perspective and the historical background, including political and doctrinal interests of the users. Jihad becomes an equivocal concept resulting the conceptual debates and doctrinal dispute. Response to this condition, it is necessary to redefine and reformulate such concepts seen from the Qur?anic perspective. This study endevours to explicate how Al-Qur?an as the Muslim?s holy book views the jihad as one of fundamental teachings in one side, and of how the Muslims as the followers implement such teachings of jihad in daily life accordingly. The article highlights that, in nature, jihad has any positive and constructive meaning as the struggle for improving the life-quality of the human beings as a whole.